Tracheal Papilloma Treated with Cryotherapy and Interferon-α: A Case Report and Review of the Literature - Fatma Yıldırım; Murat Türk; Sedat Demircan; Nalan Akyürek; Ahmet Selim Yurdakul (Case Reports in Pulmonology)
Tracheal papilloma (TP) is characterized by papillomatous growth of the bronchial epithelium that involves the trachea as a response to Human Papilloma Virus (HPV) infection. A 40-year-old male, with 3-month history of progressive dyspnea was admitted to our hospital, and there were no any other respiratory symptoms. Physical examination was unremarkable. Chest computed tomography (CT) showed that there was a papillomatous mass at the distal trachea. The lesion occupied 80% of tracheal lumen. This patient received cryotherapy and mechanical debridement under general anesthesia and postoperative pathology showed endotracheal papillomatosis. Patient was treated with interferon-α (IFN-α) and he showed no recurrence at the 8th month of his therapy.